Grain boundary segregation engineering in as-sintered molybdenum for improved ductility. (November 2018) - Leitner (née Babinsky), K.; Lutz, D.; Knabl, W.; Eidenberger-Schober, M.; Huber, K.; Lorich, A.; Clemens, H.; Maier-Kiener, V.
Abstract: The characteristics of grain boundaries and their influence on the mechanical properties have become key issues in recent research on structural materials. Especially in molybdenum, grain boundary segregation plays a significant role regarding ductility and strength. In this study as-sintered conditions of technically pure as well as boron and carbon doped molybdenum were mechanically characterized by bending tests and correspondingly analyzed by atom probe tomography to understand the differences in mechanical behavior after alloying. Strategies for improving the ductility of molybdenum are discussed with special focus on grain boundary segregation. Graphical abstract: Unlabelled Image